The Impact Of Halal Labels, Digital Marketing, and Brand Ambassadors On The Purchase Intention Of Wardah Cosmetic Products In Masamba - Nur Cahya Indah Mulia; Suhardi M anwar; Edi Maszudi (International Journal of Management and Business Economics, 2026)
This study aims to analyze the influence of halal labeling, marketing digital marketing, and brand ambassadors on consumer purchase intention for Wardah products in Masamba. This study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to 120 respondents who were users or potential users of Wardah products in Masamba. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results showed that the model explained 26.0% of the variance in purchase intention (R² = 0.260). Hypothesis testing revealed that halal labeling had no significant effect on purchase intention (β = -0.028; p = 0.773), while digital marketing had a positive but insignificant effect (β = 0.235; p = 0.051). In contrast, brand ambassadors had a positive and significant effect on purchase intention (β = 0.372; p = 0.001). These findings indicate that brand ambassadors are the most influential factor in increasing consumer purchase intention compared to halal labels and digital marketing. This study provides practical implications for companies to optimize the use of credible brand ambassadors who are aligned with the brand image. increase consumer purchasing intentions